Characteristics and Determinants of Internal Labor Mobility in Ukraine - Kupets, Olga (World Bank, Washington, DC, 2017)
Over the past 20 years Ukraine experienced fundamental structural changes due to transition to a market economy and integration with the world. Transition reforms accompanied by the collapse of traditional trade and production links with the other republics of the former USSR and Comecon countries entailed asymmetric effects on regions, reflecting an uneven distribution of winners and losers from transition. Geographical mobility of labor is one of the major mechanisms (alongside with capital mobility, wage and price flexibility, and institutional mechanisms for redistributing income across regions) in facilitating regional adjustment to idiosyncratic shocks. The ability of workers to move freely from one geographical location to another inside the borders of their country, in pursuing the same occupation or changing occupations, is of particular importance for efficient matching of labor demand and supply and reducing structural unemployment. This paper seeks to fill gap in the literature on patterns of internal labor mobility in Ukraine, its main characteristics and potential for reducing persistent regional labor market disparities and imbalances in economic and human development. The next chapters of the paper are organized as follows: second chapter evaluates the magnitude of disparities in regional labor market and socio-economic indicators over time, with a special focus on its potential impact on decision of individuals to migrate to another settlement; third chapter provides an overview of the available data sources on internal labor mobility in Ukraine, quantifies internal migration based on aggregate administrative data, discusses its trends over time and compares it levels to those found in developed and transition economies. Fourth chapter provides multivariate statistical analysis of the determinants of inter-regional migration in 2002-2010 based on administrative region-level data. Fifth chapter summarizes the findings of empirical studies on determinants of the migration decision of Ukrainians. Sixth chapter examines short-term labor migration including everyday commuting in 2005-2010 and measures its covariates using individual-level Labor Force Survey (LFS) data. Seventh chapter summarizes the main findings and concludes.